2018
DOI: 10.1136/bmjqs-2017-007476
|View full text |Cite
|
Sign up to set email alerts
|

Errors and discrepancies in the administration of intravenous infusions: a mixed methods multihospital observational study

Abstract: IntroductionIntravenous medication administration has traditionally been regarded as error prone, with high potential for harm. A recent US multisite study revealed few potentially harmful errors despite a high overall error rate. However, there is limited evidence about infusion practices in England and how they relate to prevalence and types of error.ObjectivesTo determine the prevalence, types and severity of errors and discrepancies in infusion administration in English hospitals, and to explore sources of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
118
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 72 publications
(130 citation statements)
references
References 19 publications
6
118
0
6
Order By: Relevance
“…This combined study draws on the observation of 3172 infusion administrations. Across those, as discussed by Lyons et al, 68 the only clear conclusion is that medication administered by gravity feed is more likely to result in patient harm than medication administered via infusion pumps. Neither the US nor the English study identified any events in which patient safety was significantly compromised, resulting in death or serious harm.…”
Section: Commonalities and Differences In Findingsmentioning
confidence: 99%
See 4 more Smart Citations
“…This combined study draws on the observation of 3172 infusion administrations. Across those, as discussed by Lyons et al, 68 the only clear conclusion is that medication administered by gravity feed is more likely to result in patient harm than medication administered via infusion pumps. Neither the US nor the English study identified any events in which patient safety was significantly compromised, resulting in death or serious harm.…”
Section: Commonalities and Differences In Findingsmentioning
confidence: 99%
“…There were 88 patient ID discrepancies, counting each once per patient. Reproduced from Lyons et al 68 © Article author(s) (or their employer(s) unless otherwise stated in the text of the article) 2018. All rights reserved.…”
Section: Rate Deviationsmentioning
confidence: 99%
See 3 more Smart Citations